One-Pot Synthesis of Tetraazamacrocyclic Complexes from the Arnold Salt - Woźny, Mateusz (Synthesis, 2018)
We present an improved synthesis of bis(hexafluorophosphate) Arnold salt, which is a synthon of triformylmethane. The salt is shown to be a substrate for the one-pot, aqueous synthesis of macrocyclic tetraiminato complexes of copper(II) and nickel(II). The synthesis of complexes is a major improvement over the original stepwise procedure, and is characterized by short reaction time, ease of product separation, scalability, and high yields.
Keywords: tetraazamacrocyclic; complexes; Arnold salt; one-pot synthesis; triformylmethane; template synthesis